Modernity and its discontents: A conversation with architect and urban planner Leon Krier - Samalavičius, Almantas (Journal of Architecture and Urbanism, 2013)
Leon Krier hardly needs to be introduced to anyone who has a professional or academic interest in the discussions of architecture and urbanism of recent decades. An internationally established architect, architectural theorist and urban planner, he is well-known not only as the author of numerous architectural and urban design projects and master-plans, but also for his defense of what is sometimes called „neo-traditional” architecture and the values that were and continue to be associated with the role and aesthetics of the architecture of past centuries. Although he has been attacked for his non-conformist views and critical attitude towards radical modernism, Leon Krier remains an important figure in discussions of architecture and urbanism, and his interests overlap with present concerns for environment and sustainable future. The talk by the editor of the journal with Leon Krier is an attempt to discuss the flaws of contemporary architectural and urban practice as well as to indicate its roots and draft some prospects for the future.